1996
DOI: 10.1007/bf00177277
|View full text |Cite
|
Sign up to set email alerts
|

Therapy of primary central nervous system lymphoma with pre-irradiation methotrexate, cyclophosphamide, doxorubicin, vincristine, and dexamethasone (MCHOD)

Abstract: Prior studies have suggested that pre-irradiation methotrexate (MTX)-based chemotherapy improves duration of response and survival in primary central nervous system lymphoma (PCNSL). To circumvent the potential emergence of drug resistance, we combined high-dose MTX with agents highly active against systemic lymphoma. Patients received three week cycles of CHOD (cyclophosphamide 750 mg/m2, doxorubicin 50 mg/m2, and vincristine 1.4 mg/m2 [2 mg maximum] on day 1; dexamethasone 10 mg/m2 days 1-5), and MTX (3.5 gm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0
1

Year Published

1997
1997
2010
2010

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(26 citation statements)
references
References 30 publications
1
23
0
1
Order By: Relevance
“…These disappointing results have led to the use of chemotherapy in combination with WBRT. Since the 1990s, numerous convergent phase II studies have shown that the addition of high-dose methotrexate (MTX)-based chemotherapy to RT results in a substantially longer survival time than with RT alone (median survival time, 2-4 years; 5-year survival rate, 20%-40%) ( Table 1) [52][53][54][55][56][57][58][59][60][61][62][63][64][65][66][67]. In contrast, adding standard chemotherapy for systemic lymphoma, such as cyclophosphamide, doxorubicin, vincristine, and prednisone (the CHOP regimen), to RT did not appear to result in longer survival than with RT alone.…”
Section: Treatment Of Newly Diagnosed Pcnslmentioning
confidence: 99%
“…These disappointing results have led to the use of chemotherapy in combination with WBRT. Since the 1990s, numerous convergent phase II studies have shown that the addition of high-dose methotrexate (MTX)-based chemotherapy to RT results in a substantially longer survival time than with RT alone (median survival time, 2-4 years; 5-year survival rate, 20%-40%) ( Table 1) [52][53][54][55][56][57][58][59][60][61][62][63][64][65][66][67]. In contrast, adding standard chemotherapy for systemic lymphoma, such as cyclophosphamide, doxorubicin, vincristine, and prednisone (the CHOP regimen), to RT did not appear to result in longer survival than with RT alone.…”
Section: Treatment Of Newly Diagnosed Pcnslmentioning
confidence: 99%
“…About half of immunocompetent patients with primary CNS lymphoma who achieve complete recovery after primary treatment suffer relapse, and the disease is refractory in 10-15%. 7,9) The prognosis for both recurrent and progressive primary CNS lymphoma is poor and most patients die within 2-4 months of neurological deterioration. 7,21) The present patient underwent further chemotherapy with rituximab and temozolomide.…”
Section: Discussionmentioning
confidence: 99%
“…The addition of CHOP or other anthracycline-containing regimens to HD-MTX produces results similar to those of HD-MTX alone, with a CR ranging from 60 to 67% and a median OS of 20 --25 months. Meanwhile, an increased toxicity is reported with these regimens [17,18].…”
Section: The Chop Regimenmentioning
confidence: 99%
“…Even if only a minority of relapsed patients are routinely assessed for meningeal recurrence, the majority of meningeal relapses seems to occur in patients with positive CSF cytology at diagnosis [8,18,29]. This has led some authorities to suggest that, to minimize toxicity, intrathecal chemotherapy should be reserved for patients with positive CSF cytology [29,52].…”
Section: Strategies To Improve Drug Bioavailability In Sanctuariesmentioning
confidence: 99%
See 1 more Smart Citation